Generation Z students’ attitudes to printed books Inertia of the historical perception process, diversification of usefulness in the DPR Korea - Kwang-Myonga, Mun; Jong-Song, Ju; Kum-Song, Kim; Chol, Pak; Paek, Sok (Politeknik Negeri Bali, 2024)
Thanks to the eye-opening innovation of the digital technology a lot of disadvantages of the e-books will be overcome in the near future, and then what role the printed books will play is a great concern for those who work in the fileds of publication, library etc. This paper has focused on the printed books and analyzed the Generation Z students’ attitudes towards them. 174 students with different majors have been interviewed using the questionnaires made by experts and the collected data has been analyzed. For the purpose of sufficient feedback from the students the second question was made open. Students still primarily perceive “books” as printed ones and have a positive attitude to the usefulness of them in the future, though they are “digital natives”. First of all, the traditional definition and image of books, social customs regarding their usefulness play a crucial role in making people have a positive attitude towards printed books even in the era of digital technology. Also the usefulness of printed books has been diversified as they are now used in a variety of forms, such as evidence or luxury things. The future study should focus on those with different social backgrounds, thus clarifying the relationship between the cultural attitudes and the printed books in detail.